Ignition of granulated mixed fuel based on lignite and wood waste; Journal of Physics: Conference Series; Vol. 1359 : Thermophysics and Physical Hydrodynamics - Yankovsky S. A. Stanislav Aleksandrovich (2019, 2019)
Title screen